A Comparative Pharmacokinetic Study of a Fixed Dose Combination for Essential Hypertensive Patients: A Randomized Crossover Study in Healthy Human Volunteers - Gorain, B.; Choudhury, H.; Halder, D.; Sarkar, A. K.; Sarkar, P.; Biswas, E.; Ghosh, B.; Pal, T. K. (Drug Research, 2013)
This study was aimed to investigate the relative bioavailability of fixed-dose-combination (FDC) product of amlodipine, telmisartan and hydrochlorothiazide with individual marketed products in healthy male volunteers. Control of blood pressure with fixed dose combination of the above drugs acting through different mechanism have a benefit of convenient dosing in terms of compliance, lower the dose and subsequently reduce the side effects.The authors investigated the relative bioavailability under a fasting state of the 3 drugs in a randomized, open-label, 2-treatment, 2-period, 2-sequence, crossover bioequivalence study with a washout period of 21 days. Plasma concentration of the analytes were assayed in timed samples with a simple, highly sensitive and rapid validated method using HPLC coupled to tandem mass spectrometry that had a lower limit of quantification of 1 ng/mL for all the 3 components.Test and reference formulations gave a mean Cmax of 5.234±0.914 ng/mL and 4.991±0.563 ng/mL, 108.839±13.601 ng/mL and 114.783±12.315 ng/mL and 97.814±10.779 ng/mL and 93.731±10.018 ng/mL for amlodipine, telmisartan and hydrochlorothiazide respectively. The AUC0-t of amlodipine, telmisartan and hydrochlorothiazide was 161.484 ng.h/mL, 1 917.644 ng.h/mL and 822.847 ng.h/mL for test formulation and 162.108 ng.h/mL, 2 014.764 ng.h/mL and 829.323 ng.h/mL for reference in the fasting state.The 90% confidence intervals for the test/reference ratio of the pharmacokinetic parameters in fasting state (mean Cmax, AUC0-t, and AUC0-∞) were within the acceptable range of 80.00–125.00. Thus, these findings clearly indicate that the FDC product is bioequivalent with the individual marketed products in terms of rate and extent of drug absorption and is well tolerated with no significant adverse reactions.
Keywords: hypertension; bioavailability; amlodipine; telmisartan; hydrochlorothiazide; pharmacokinetics